The impact of pretreatment and inoculum to substrate ratio on methane potential of organic wastes from various origins - Yoruklu, Hulya Civelek; Korkmaz, Emre; Demir, Neslihan Manav; Ozkaya, Bestami; Demir, Ahmet (SPRINGER, 2018)
Biochemical methane potentials (BMP) of two different substrates from macroalgae (MA) and market place wastes (MPW) were investigated using anaerobic granulated sludge from food industry with different ratios of substrate to inoculum (S/X). The substrates were used as MA only, MPW only, MA-MPW mixture, pretreated MA, and pretreated MA-MPW mixture. Research involved investigation of the effects of parameters such as temperature (35, 45, and 55 A degrees C), substrate to inoculum ratio (S/X = 0.5, 2.0, 4.0, and 6.0 as g VSsubstrate/g VSinoculum), and the type of pretreatment (by microwave, thermal, and ultrasonic) on BMP. BMP assays were performed for all substrates. The highest cumulative biogas production (and BMP) were obtained for MA only at an S/X ratio of 4.0 g VS/g VS as 357 L-biogas/kg VS (197 L CH4/kg VS) and 33 L-biogas/kg VS (17 L CH4/kg VS), respectively, at 35 and 55 A degrees C. For pretreated substrates, the highest cumulative biogas production and BMP were observed as 287 L-biogas/kg VS and 146 L CH4/kg VS using pretreated macroalgae at 35 A degrees C. Results suggested that MA only and MA-MPW mixtures are suitable substrates for biogas production. It is also concluded that any type of pretreatment has adverse effects on biogas and methane productions.
Keywords: Anaerobic treatment; Biochemical methane potential (BMP); Macroalgae; Market place waste; MUNICIPAL SOLID-WASTE; BIOGAS PRODUCTION; ANAEROBIC-DIGESTION; THERMAL PRETREATMENT; FOOD WASTE; CO-DIGESTION; BMP TESTS; BIOMASS; SEAWEED; HYDROLYSIS; Environmental Sciences & Ecology